2021
DOI: 10.1029/2021gl095850
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic Debris Remains in the Orogen Despite a Decade of Enhanced Landsliding

Abstract: Coseismic landslides triggered by major continental earthquakes can generate large quantities of debris over vast areas, by displacing soil and regolith as well as bedrock (Fan, Scaringi, Korup, et al., 2019). The evacuation of landslide-derived sediment cascades influences the erosion budget of orogens in short and long terms. The distribution of steep slopes and high shaking intensities can explain, to first order, areas and volumes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Still, larger time spans are characteristic of landscape recovery in arid regions (Wolman & Gerson, 1978). Several studies have reported that landslide scars can recover over 10 years in South China with abundant rainfall (Dai et al, 2021; Fan et al, 2018). It could be predicted that landslide scars would remain exposed and suffer rill erosion in the next few years in our study region, which is located in Northwest China, with less rainfall for plant recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, larger time spans are characteristic of landscape recovery in arid regions (Wolman & Gerson, 1978). Several studies have reported that landslide scars can recover over 10 years in South China with abundant rainfall (Dai et al, 2021; Fan et al, 2018). It could be predicted that landslide scars would remain exposed and suffer rill erosion in the next few years in our study region, which is located in Northwest China, with less rainfall for plant recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, frequent shallow landslides reactivation, along with climate change and frequent rainstorms, made it difficult for scars to heal (Figure 12a–f). After the landslides, the increased slope degree of the hillslope and changed soil hydraulics led to a decrease in the trigger threshold of the new landslide (Dai et al, 2021). Landslides are more active and frequent in the context of increased rainstorms in this region (Tang et al, 2020; Zhuang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This means that our time series represents a precautionary scenario that will likely overestimate hazard persistence relative to studies that only document new or substantially‐altered source areas. However, we know that the majority of coseismic landslide deposits remain in place on hillslopes for years after a large earthquake, with estimates for Wenchuan ranging between 80 to 90% of the initially mobilized material still being in situ after 6–7 years (Dai et al, 2021; Fan, Domènech, et al, 2018; Huang & Li, 2014; Märki et al, 2021; Zhang & Zhang, 2017). Even though the proportion of this material that is readily erodible will decrease through time (Domènech et al, 2019; Qu, 2019; Yunus et al, 2020), longer‐term studies have demonstrated that elevated rates of debris flows can persist for decades (Li et al, 2018; Ni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On May 31st, 1970, a snow avalanche caused by the Peru earthquake directly buried the city of Yungay, causing approximately 23,000 death. As a result, earthquake-induced landslides have received widespread attention in recent decades, and related studies has primarily focused on the construction of landslide inventories (Shao et al, 2023;Zhao et al, 2021), distribution pattern (Jibson and Tanyaş, 2020; Papathanassiou et al, 2021), susceptibility and hazard assessment (Lombardo et al, 2019;Robinson et al, 2017;Shao et al, 2021), and landscape evolution (Dai et al, 2021;Parker et al, 2011). Among them, earthquake-induced landslide hazard mapping plays an important role in emergency rescue and disaster recovery and reconstruction (Ma et al, 2020;Massey et al, 2018;Shao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%